BULLYING AND CYBERBULLYING: WHEN THE MORAL VALUES ARE LACKING AND THE COEXISTENCE IS SHAKING - Paulino Tognetta, Luciene Regina [UNESP]; Knoener, Darlene Ferraz [UNESP]; Bicudo Bomfim, Sanderli Ap. [UNESP]; De Nadai, Sandra Trambaiolli [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
This theoretical study aims to highlight the absence of moral content in situations of bullying and cyberbullying, emphasizing, on the other hand, the need to understand this phenomenon of violence as a moral problem. In a context of violent interpersonal relations experienced in educational institutions, whether face-to-face or virtual form, it is urgent to highlight the evidences of the current investigations on this subject that aim to overcome the problem through processes that prioritize the composition of an environment that favors moral formation and ethical coexistence. Since the school is very important in building the morality of its students, there must be, in every educational institution, the consolidation of a project of ethical living, in order to make explicit the pact of all its characters with the prevention of violence. The current literature indicates the need for programs and projects of ethical coexistence that are intentional, systematized and continuous, providing spaces of protagonism of the students, in order to exercise and experience moral values so that they will be priority in their personality precisely by highlighting how much these values are absent in those who attack as well as often in those who receive or witness the aggression.
Keywords: Bullying; Cyberbullying; Moral values; Coexistence; Teacher's training